IMPROVING STUDENTS' MATHEMATICAL CRITICAL THINKING ABILITY AND RESILIENCY USING PROBLEM-SOLVING APPROACH - Rizky Laili Maulani; H.E.T Ruseffendi (PRISMA, 2019)
The background of this research is the low ability of reasoning, critical thinking, and mathematical resilience of SMPN students in Cimahi City. The purpose of this research is to analyze the role of problem-solving approach to critical thinking ability and mathematical resilience. This study was an experimental study with a pretest post control group design and involved 65 eighth grade students from SMPN 8 Cimahi who were randomly selected for school and class. The instrument used in this research is the test of critical mathematical thinking ability, as well as the scale of mathematical resilience. This study found that the improvement of critical thinking ability of mathematics students who get learning with the problem-solving approach is not better or equal to students taught by conventional learning, while the mathematical resilience of students who get learning with the problem-solving approach is not better or equal to students who are taught with conventional learning. In addition, there is no association between critical thinking ability and mathematical resilience. Another finding that students are still difficult in solving the problem of critical mathematical thinking skills.